Figurative Language in English Song “Die With A Smile” Viewed A Conceptual Metaphor Theory - Aprilyanti, Hilda Rachma; Prasetyo, Yudy; Aisyah, Siti (ITScience (Information Technology and Science), 2026)
This research aims to identify the types of figurative language and to describe the conceptual meanings based on Conceptual Metaphor Theory in the song “Die With a Smile” by Lady Gaga and Bruno Mars. This study employed a descriptive qualitative method using a cognitive semantic approach. The data were analyzed by classifying the types of figurative language and mapping metaphoric expressions into source and target domains based on Conceptual Metaphor Theory proposed by Lakoff & Johnson (1980). The results show that the song contains metaphor, hyperbole, personification, simile, and repetition, with metaphor as the most dominant type. Based on Conceptual Metaphor Theory, the metaphors are categorized into structural, ontological, and orientational metaphors, with structural metaphors appearing most frequently. Dominant conceptual meanings include “love is a journey,” “love is war,” and “death as fulfillment,” representing emotional struggle, loyalty, urgency, and satisfaction in romantic relationships. These metaphors demonstrate how abstract emotions and romantic experiences are conceptualized through concrete and embodied human experiences. This study concludes that figurative language in the song plays an important role in expressing human cognition, emotions, and life experiences through metaphorical structures, making Conceptual Metaphor Theory (CMT) an effective framework for identifying and describing meaning in popular song lyrics.